Whether Serum Glial Fibrillary Acidic Protein (GFAP) Can Be Used as a Diagnostic Biomarker in Patients With Glioblastoma? - Charandeep Singh Gandhoke; Ankit S Shah; Daljit Singh; Manju Subberwal; Rohit Kumar Gupta; Vinod Kumar Gupta; Ravindra K Saran (MAMC Journal of Medical Sciences, 2020)
Aim: To study if there is an increase in the serum levels of Glial Fibrillary Acidic Protein (GFAP) in patients with glioblastoma so that it can be used as a diagnostic biomarker for these cases. Design: Prospective observational study. Material and Methods: We prospectively examined 193 patients, out of which 25 were controls (patients with degenerative spinal disease or CV junction anomaly), 79 were tumors other than glioma, 45 were histologically proven gliomas except glioblastoma and 44 were histologically proven glioblastomas. Serum was taken from the patients in the pre-operative period. Serum GFAP levels were determined using a biotin-labeled antibody-based sandwich enzyme immunoassay for the quantitative measurement of GFAP in ng/ml. Statistical Analysis: Data analysis was performed by using SPSS (Statistical Package for Social Sciences) version 20:0. Statistical significance was defined as P value < 0.05. Receiver operating characteristic (ROC) curve analysis was used to find the cut-off value of serum GFAP for glioblastoma patients. Results: In Group A (25 controls) and Group B (79 patients with non-glial brain tumors), no patient had detectable levels of GFAP in their serum. Out of the 45 patients with histologically proven gliomas except glioblastoma (Group C), 12 patients had raised serum GFAP levels. Out of the 44 patients with histologically proven glioblastomas (Group D), 38 patients had raised serum GFAP levels while in the remaining 6, the levels of serum GFAP were not detectable. The sensitivity of serum GFAP levels in diagnosing glioblastoma patients was 86.36% and the specificity was 91.95%. The diagnostic accuracy of the test was 90.67%. Conclusions: Serum GFAP is a sensitive and specific marker for glioblastoma and can be a useful pre-operative serum biochemical investigation in differentiating glioblastoma cases from other brain tumors.